Unraveling the chemosensory characteristics of strong-aroma type Baijiu from different regions using comprehensive two-dimensional gas chromatography–time-of-flight mass spectrometry and descriptive sensory analysis. (30th November 2020) - He, Yingxia; Liu, Zhipeng; Qian, Michael; Yu, Xiaowei; Xu, Yan; Chen, Shuang
Highlights: Sensory and chemical profiles of strong-aroma type Baijiu from different regions. 58 compounds were identified as potential markers of regional strong-aroma type Baijiu. Relationships between potential aroma compounds and sensory attributes were shown. Abstract: Comprehensive 2D gas chromatography–time-of-flight mass spectrometry was combined with descriptive sensory analysis to elucidate the specificity of strong-aroma type Baijiu (Chinese liquor) from different regions, based on regionally distinct flavor characterized by chemical and sensory profiles. Numerous potential aroma compounds (262) were identified, among which 58 aroma compounds were significantly different between the samples from Sichuan and Jianghuai regions. Relationships between these potential aroma compounds and sensory attributes were investigated by partial least squares regression and network analysis. The compounds that dominantly contributed to the important sensory attributes were identified. The high pyrazines, furanoids, and carbonyls amounts contributed to the high intensities of the cellar, toasted, and grain aroma profiles of the Sichuan region samples, while the high ester and alcohol levels contributed to the fruity and floral aroma profiles of the Jianghuai region samples. This approach may have practical application in flavor characterization of other alcoholic beverages.